Local Anesthesia at ST36 to Reveal Responding Brain Areas to deqi - Ling-min Jin (Evidence-Based Complementary and Alternative Medicine, 2014)
Background. Development of non-deqi control is still a challenge. This study aims to set up a potential approach to non-deqi control by using lidocaine anesthesia at ST36. Methods. Forty healthy volunteers were recruited and they received two fMRI scans. One was accompanied with manual acupuncture at ST36 (DQ group), and another was associated with both local anesthesia and manual acupuncture at the same acupoint (LA group). Results. Comparing to DQ group, more than 90 percent deqi sensations were reduced by local anesthesia in LA group. The mainly activated regions in DQ group were bilateral IFG, S1, primary motor cortex, IPL, thalamus, insula, claustrum, cingulate gyrus, putamen, superior temporal gyrus, and cerebellum. Surprisingly only cerebellum showed significant activation in LA group. Compared to the two groups, bilateral S1, insula, ipsilateral IFG, IPL, claustrum, and contralateral ACC were remarkably activated. Conclusions. Local anesthesia at ST36 is able to block most of the deqi feelings and inhibit brain responses to deqi, which would be developed into a potential approach for non-deqi control. Bilateral S1, insula, ipsilateral IFG, IPL, claustrum, and contralateral ACC might be the key brain regions responding to deqi.